THE ROLE OF PROGRAM MANAGER AND CREATIVE MANAGER IN “TILIK JIWA” CAMPAIGN STRATEGY TO INCREASE AWARENESS AND PARTICIPATION IN MENTAL HEALTH SCREENING SERVICES BY DINAS KESEHATAN KOTA SEMARANG - Azizah Charis Hanifah; Lintang Ratri Rahmiaji (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This project was designed against the background of the high prevalence of mental health disorders in the community, while public awareness and participation in mental health screening facilitated by Dinas Kesehatan Kota Semarang remains low. This situation indicates a gap between the need for and use of services. Therefore, the Tilik Jiwa communication campaign was designed using a social marketing approach to increase awareness and knowledge and encourage community participation in utilizing these services. In addition, it aims to reduce the negative stigma surrounding mental health in the community. The campaign evaluation results show an increase in awareness of 87.79 percentage points, an increase in knowledge of 89.33 percentage points, a decrease in stigma of up to 12.3%, and an increase in community participation in the use of mental health screening services of 36%. In this campaign, the Program Manager is responsible for coordinating the entire campaign and ensuring alignment between planning and implementation of activities. The Creative Manager ensures that the development of creative concepts and key messages to be conveyed in the campaign are in line with the characteristics of the younger generation, especially those aged 19-25 as the main target audience of Tilik Jiwa campaign.